2020
DOI: 10.1088/1748-9326/ab6fbe
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing smart-meter data to project impacts of urban warming on residential electricity use for vulnerable populations in Southern California

Abstract: Extreme heat events are increasing in frequency and intensity, challenging electricity infrastructure due to growing cooling demand and posing public health risks to urbanites. In order to minimize risks from increasing extreme heat, it is critical to (a) project increases in electricity use with urban warming, and (b) identify neighborhoods that are most vulnerable due in part to a lack of air conditioning (AC) and inability to afford increased energy. Here, we utilize smart meter data from 180 476 households… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…We estimate potential benefits and co-benefits of urban afforestation to better quantify the importance of such nature-based solutions beyond surface urban heat island mitigation. For this analysis, California is an ideal location due to widespread data availability, the state's susceptibility to heatwaves, and a rich scientific literature on the impact of urban afforestation (Chen et al, 2020;Hulley et al, 2020;McPherson et al, 2017;Shonkoff et al, 2011). While there are additional benefits to biodiversity, groundwater recharge, etc., we primarily focused on addressing tree cover inequality while benefiting the vulnerable populations exposed to excess urban heat and climate change 16 .…”
Section: Examining Benefits and Co-benefits Of Urban Afforestationmentioning
confidence: 99%
See 3 more Smart Citations
“…We estimate potential benefits and co-benefits of urban afforestation to better quantify the importance of such nature-based solutions beyond surface urban heat island mitigation. For this analysis, California is an ideal location due to widespread data availability, the state's susceptibility to heatwaves, and a rich scientific literature on the impact of urban afforestation (Chen et al, 2020;Hulley et al, 2020;McPherson et al, 2017;Shonkoff et al, 2011). While there are additional benefits to biodiversity, groundwater recharge, etc., we primarily focused on addressing tree cover inequality while benefiting the vulnerable populations exposed to excess urban heat and climate change 16 .…”
Section: Examining Benefits and Co-benefits Of Urban Afforestationmentioning
confidence: 99%
“…Here we estimate this decrease in energy consumption by combining estimates of urban AC saturation rate by California's Building Climate zones (ACp,z), with the sensitivities of electricity consumption to ambient temperature (T) and estimates of number of housing units (Hi) from the census data. The AC saturation rate is from Chen et al (Chen et al, 2020) based on reported utility data throughout California. This includes central air conditioning, room AC, and evaporative coolers.…”
Section: Reduced Urban Energy Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…With 42% of US residential use due to space conditioning, ambient temperature is a primary driver of residential electricity use, especially with high air conditioning penetration [15,18,19]. Despite the mild climate in Southern California, Chen et al assessed a substantial (69% estimated) regional household penetration for air conditioning [19,20]. This includes residential air conditioning systems in different form factors and cooling capacities.…”
Section: Introductionmentioning
confidence: 99%